Silencing fibroblast growth factor 7 inhibits krypton laser‐induced choroidal neovascularization in a rat model. Issue 8 (24th April 2019) - Zhang, Chao; Han, Mei; Wu, Shuai
Abstract: Choroidal neovascularization (CNV), a characteristic of age‐related macular degeneration, is an underlying cause of severe vision loss among elderly patients. Fibroblast growth factor (FGF) is suggested to exert an important role in the pathogenesis of CNV. However, the molecular mechanisms governing this event are not fully elucidated. Herein, we identified the potential role of FGF7 in CNV. To examine the roles of FGF7 in the progression of CNV, rat CNV models were established and treated with small interfering RNA (siRNA) against FGF7 or FGF7 overexpression, followed by identification of expression of FGF7 in the CNV modeled rats. Next, proliferation and migration, and in vitro tube formation of human umbilical vein endothelial cells, as well as expression of vascular endothelial growth factor (VEGF) and transforming growth factor‐beta 2 (TGF‐β2) were evaluated. CNV led to upregulated FGF7 expression. Cells in the presence of FGF7 siRNA showed suppressed proliferation, migration, and tube formation, along with downregulated VEGF and TGF‐β2 expression. Taken together, functional suppression of FGF7 inhibited the onset of CNV, ultimately highlighting a novel therapeutic target for suppressing CNV progression. Abstract : Taken together, functional suppression of fibroblast growth factor (FGF)7 inhibited the onset of choroidal neovascularization (CNV), ultimately highlighting a novel therapeutic target for suppressing CNV progression.